1988
DOI: 10.1515/znc-1988-9-1025
|View full text |Cite
|
Sign up to set email alerts
|

Identifizierung und Synthese von Dimethylalkanen als Sexuallockstoffe weiblicher Miniermotten (Lyonetiidae) / Identification and Synthesis of Dimethylalkanes as Sex Attractants of Female Leaf Miner Moths (Lyonetiidae)

Abstract: 5,9-Dimethylheptadecane and 5,9-dimethylpentadecane represent major components of the sex pheromones of females of the leafminer moths Leucoptera scitella and Perileucoptera coffeella respectively; 5,9-dimethylhexadecane was found in both species as a minor component. These branched chiral hydrocarbons represent a new type of Lepidopteran pheromones, for which simple syntheses are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…L. monacha also secrets an unbranched derivative (epo7-18:H) [97], and a C 20 analog (Me2,epo7-20:H) has recently been found in females of another related species, L. xylina [98]. In addition to the epoxides, six methyl-branched hydrocarbons with a C 15 -C 18 main chain have been identified from four micro-lepidopteran species in Lyonetiidae (Yponomeutoidea) [99][100][101][102][103]. These Lyonetiidae pheromones possess one methyl group at the common 5-position, because the 14-position of 1,Me14-18:H and 1,Me10,Me14-18:H is represented as the 5-positon counting from the opposite terminal methyl group.…”
Section: Structures Of Other Female Pheromonesmentioning
confidence: 99%
“…L. monacha also secrets an unbranched derivative (epo7-18:H) [97], and a C 20 analog (Me2,epo7-20:H) has recently been found in females of another related species, L. xylina [98]. In addition to the epoxides, six methyl-branched hydrocarbons with a C 15 -C 18 main chain have been identified from four micro-lepidopteran species in Lyonetiidae (Yponomeutoidea) [99][100][101][102][103]. These Lyonetiidae pheromones possess one methyl group at the common 5-position, because the 14-position of 1,Me14-18:H and 1,Me10,Me14-18:H is represented as the 5-positon counting from the opposite terminal methyl group.…”
Section: Structures Of Other Female Pheromonesmentioning
confidence: 99%
“…3 The sex pheromone was previously identified as 5,9-dimethylpentadecane (1). 4 Several aspects of pheromone biology may change significantly with age. In some species, most females initiate calling within 24 h of emergence, 5,6 while in other individuals vary considerably in the age at which calling starts.…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, Wittko Francke recognised that the main component of the sex attractant of females is 5,9-dimethylpentadecane. [188] Field studies with monitoring traps, which contained the different stereoisomers, revealed the (5S,9R)-isomer as the most active component. [189] For practical applications, the mixture of diastereomers can be used none the less.…”
Section: Coffee Leaf Minermentioning
confidence: 98%